Pengaruh Komunikasi Persuasif terhadap Kesuksesan Sosialisasi Kebijakan Publik di Kalangan Masyarakat Perkotaan - indah yulianti; Chyntia wongso; Sabrina Rosa Aidia (Dialogika : Jurnal Penelitian Komunikasi dan Sosialisasi, 2025)
Persuasive communication is an important strategy in conveying public policy to urban communities that tend to be busy and diverse. This study examines the role of persuasive techniques in increasing understanding and support for policies to reduce the use of single-use plastics. Using an experimental method, the results of the study show that messages delivered with emotional narratives and scientific facts have the most significant impact.